Analysis of the Water Quality Status of the Belalo River in Lasolo District, North Konawe Regency - Roy Saputra Ammai; Ridwan Adi Surya; Junartin Teke; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
The existence of land use around rivers can affect the quality of river water. Various land uses, such as agricultural land and residential areas, accompanied by diverse activities such as sago processing, washing, and bathing, can impact river quality and public health risks. This study aims to determine the water quality status of the Belalo River in Lasolo District, North Konawe Regency, using the pollution index method as regulated in the Decree of the Minister of Environment of the Republic of Indonesia Number 115 of 2003 concerning Guidelines for Determining Water Quality Status. This research method refers to the class II quality standards set out in the Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Administration of Environmental Protection and Management. The research was conducted in June 2025. The results of this study indicate that Station I falls into the category of meeting quality standards with a Pollution Index value of 0.51. Station II falls into the category of meeting quality standards with a Pollution Index value of 0.48, and Station III falls into the category of meeting quality standards with a Pollution Index value of 0.85. The parameter that does not meet class II quality standards is a chemical parameter, namely Biochemical Oxygen Demand (BOD), which is present at Station III.